Do not make me roll initiative: Assessing the Big Five characteristics of Dungeons & Dragons players in comparison to non-players - Lorenz, Timo; Hagitte, Leonie; Brandt, Melvin (Frontiers in Psychology, 2022)
The so-called geek-culture becomes increasingly more mainstream, and its social and economic impact is growing. In contrast, there is very little quantitative psychological research on this subculture and the people immersed in it. The aim of this study was to investigate whether there are differences in the Big Five personality factors between Dungeons & Dragons players and non-players. Within a sample of 801 individuals – 399 Dungeons & Dragon players and 402 non-players - the results indicated that Dungeons & Dragons players show statistically significant higher scores in extraversion as well as in openness to new experiences. Furthermore, we found a statistically significant correlation between Dungeons & Dragons players’ scores in extraversion and their character’s charisma. The results are in line with more recent findings from Big Five research in the geek-culture and contradict older findings regarding a low extraversion and high neuroticism of Dungeons & Dragon players.